URGENSI GUARANTEE OFF TAKERS DALAM MENINGKATKAN INVESTASI MINYAK DAN GAS - Muhammad Irfan Hilmy; Nibraska Aslam; Dinda Jhaneta; David Brian Leong Retna (Hang Tuah Law Journal, 2022)
The investment climate for oil and gas mining since 2000 has continued to decline until now. This can be attributed to various factors, one of which is the lack of certainty regarding buyers of oil and gas at the downstream stage. This will certainly have an impact on the development of oil and gas mining, so that it can have a wider impact on welfare aspects. This study will discuss the urgency and reasons for the inclusion of a guarantee off taker as one of the clauses in an oil and gas contract. This study uses a normative method with a statutory and conceptual approach. This study found that there are at least 3 dimensions of urgency and reasons for the inclusion of an off takers guarantee clause, namely the dimension of people's livelihood based on Article 33 paragraph (3) of the 1945 Constitution which mandates efforts for people's welfare because through large investments people's welfare should also increase. Next is the dimension of the oil and gas business which has a high risk that requires certainty in selling oil and natural gas. The last dimension is the investment dimension.